Editorial to the Special Issue - Torsten Niechoj; Özlem Onaran; Sabine Reiner (Intervention. European Journal of Economics and Economic Policies, 2012)
In 2012, public debt is still at the centre of attention and economic policies – globally, but especially in Europe. For most of the mainstream commentators the main source of public debt can be traced back to loose public spending behaviour and a lack of fiscal discipline. However, story and facts do not coincide perfectly, to say the least (see also the contributions by Ederer in the forum section of this issue and Niechoj and van Treeck 2011 in the last issue of this journal). To give only one example taken from the European case: In Spain the level of public debt is still below the German level although Germany is the main proponent and an example of presumably sound fiscal policy and a successful recovery after the financial market crisis from the point of view of both the public and mainstream academia. Additionally, the debt-to-GDP ratio of Spain had been falling until 2007, down to only 36 per cent, which is quite low in international comparison and far below the debt criterion of the European Stability and Growth Pact.
Keywords: 330